Enumeration for spanning trees and forests of join graphs based on the combinatorial decomposition - Sung Sik U (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
This paper discusses the enumeration for rooted spanning trees and forests of the labelled join graphs $K_m+H_n$ and $K_m+K_{n,p}$, where $H_n$ is a graph with $n$ isolated vertices.